Perancangan dan Implementasi Aplikasi Pemesanan Tiket Pada PT. Ayah Ibu Tranport Berbasis Android - Mursyidul Haq; Yuhefizar; Rita Afyenni (Ikatan Ahli Informatika Indonesia, 2021)
Ayah Ibu Transport is a transportation company in Payakumbuh. Over time, passenger demand at PT. Ayah Ibu Transport continues to increase, the increase in passengers affects administrative services to passengers both in terms of information and time of ordering. Management of departure schedules, ticket prices, and other information has become increasingly complex from time to time. To help solve problems with increasingly complex administrative services, a ticket booking application at PT. Ayah Ibu Transport based on android. The goal is to make it easier for prospective passengers to order tickets, making it easier for the admin of PT. Father and Mother of Transportation in managing bookings and reducing the number of queues in ticket bookings. This application is made by data collection methods, application design, application development with Android Studio tools using Kotlin programming language on the Android section and PHP language on the server side. Thus this application can make it easier for prospective passengers and admins to carry out the order management process while reducing queues.